2016
DOI: 10.1123/kr.2016-0027
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Instruction and Reducing Costs: Chico State University’s Approach to Course Redesign

Abstract: In 2009, California State University-Chico implemented a unique system of course redesign with the aim of improving student learning, increasing instructional efficiency, and reducing university costs. Inspired by and modeled after the National Center for Academic Transformation, the “Academy e-Learning” program involves a 3-week training covering models of course design, learning theories, assessment methods, and a host of instructional technologies. This paper summarizes data from 40 courses, across five sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…According to the sample students, the role of instructors is multifaceted; their constant presence, guidance, facilitation, management, clear instructions, scaffolding and support are all much needed. This agrees with the results from the literature, according to which instructors should interact with students via synchronous and asynchronous means (Bolliger & Martin, 2018;Heilporn & Desrochers, 2020) and provide adequate instructions and feedback (Afifi & Alamri, 2014;Ng & Baharom, 2018); additional face-to-face support can have a positive impact on learners' comprehension (Trout & Vela, 2016). In our research, students found the teleconferencing sessions especially useful.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…According to the sample students, the role of instructors is multifaceted; their constant presence, guidance, facilitation, management, clear instructions, scaffolding and support are all much needed. This agrees with the results from the literature, according to which instructors should interact with students via synchronous and asynchronous means (Bolliger & Martin, 2018;Heilporn & Desrochers, 2020) and provide adequate instructions and feedback (Afifi & Alamri, 2014;Ng & Baharom, 2018); additional face-to-face support can have a positive impact on learners' comprehension (Trout & Vela, 2016). In our research, students found the teleconferencing sessions especially useful.…”
Section: Discussionsupporting
confidence: 91%
“…Authentic content can be drawn from real-life experiences, with specific examples, directing students towards the active application of knowledge to develop skills relevant to their academic and professional fields (Bolliger & Martin, 2018;Britt, 2015;Rhim & Han, 2020;Ritzhaupt et al, 2020;Sugar & Luterbach, 2016;Trespalacios & Lowenthal, 2019). It is important, though, to follow a differentiated instruction, by adapting the resources to fit students' distinctive traits and abilities (Sugar & Luterbach, 2016;Trout & Vela, 2016), such as modifying the interface for learners in need of support.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations